(untitled) (Journal of the College of Basic Education, 2025)
Taking the art of ceramics on his shoulders to match the function and beauty because of its composition and its first creation to beautify things through the use of elements used in daily life. The mythological character represents the pure art with aesthetic features, adding the richness of the legend to the system, to the overlap of the technical and aesthetic performance in the ceramic works of reading them within contemporary trends. We reveal the links between the previous concepts as the performance systems called in contemporary ceramic art to frame contemporary achievements in contemporary Iraqi ceramics. Technical and intellectual practices with a view to departing from the current pattern by introducing new intellectual compressors such as glazing techniques or preparing certain types of coatings for different burning methods. The current research aims to: 1 - inventory and identify the most important aesthetic variants produced by the potter in his technical experience (convergence, metaphor, Westernization) to reach a variety in its technical results. 2 - Identify the factors present strongly in his artistic and intellectual performances as stressful references such as (religious factor, social worker, political factor, etc.). The researcher followed the analytical descriptive method and the ceramic works were limited to (40) ceramic works, which were adopted over three decades of the artist’s life. Eight (8) works were selected after they were reviewed by the experts. Out of (40) works. They were selected on the basis of The researcher reached a number of conclusions, the most important of which are: Ceramic potter movement took a short period of time in the last century and nourished this movement in the light of the aesthetics of performance with its vitality and techniques in its works. The performance of the art of ceramics in the time of modernity is enthusiastic because it shows the abilities of the artist as a creator and manufacturer of his artistic achievements and his natural landscape and physical and social entity more inclined to the skills of performance.